2015
DOI: 10.1021/acs.jpcb.5b01593
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Protein Hydration, Glass Transitions, and Structural Relaxations of Aqueous Protein and Carbohydrate–Protein Systems

Abstract: Water distribution and miscibility of carbohydrate and protein components in biological materials and their structural contributions in concentrated solids are poorly understood. In the present study, structural relaxations and a glass transition of protein hydration water and antiplasticization of the hydration water at low temperatures were measured using dynamic mechanical analysis (DMA) and differential scanning calorimetry (DSC) for bovine whey protein (BWP), aqueous glucose-fructose (GF), and their mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Interestingly, in the case of T4-lysozyme, which does not show the discontinuity, the EPR saturation parameters of the spin-labeled side chain at position 96 indicate a smooth transition around 190 K (Figure B). Such a smooth transition of the relaxation properties around T g points to a microenvironment characterized by low fragility, and it is consistent with the broad range of T g values (160–190 K) found in hydrated protein systems (for recent reviews, see refs and ). In particular, for hydrated lysozyme, an approximate T g ∼ 180 ± 15 K was reported (see, for example, ref ), which originates from the collective motion due to the so-called main structural relaxation (α-relaxation) in hydrated proteins (for two recent reviews, see refs and ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the case of T4-lysozyme, which does not show the discontinuity, the EPR saturation parameters of the spin-labeled side chain at position 96 indicate a smooth transition around 190 K (Figure B). Such a smooth transition of the relaxation properties around T g points to a microenvironment characterized by low fragility, and it is consistent with the broad range of T g values (160–190 K) found in hydrated protein systems (for recent reviews, see refs and ). In particular, for hydrated lysozyme, an approximate T g ∼ 180 ± 15 K was reported (see, for example, ref ), which originates from the collective motion due to the so-called main structural relaxation (α-relaxation) in hydrated proteins (for two recent reviews, see refs and ).…”
Section: Discussionmentioning
confidence: 99%
“…Bovine whey proteins have very complex protein structures and consist of β-lactoglobulin~50%, α-lactalbumin~20%, bovine serum albumin~10% as well as smaller quantities of lactoferrin and other proteins. A mix of whey proteins does not have clear representative T g (Maidannyk & Roos, 2016;Roos & Potes, 2015). Carbohydrate solids and proteins, as glass-forming food components, are often used to obtain hydrophilic encapsulant solid matrices, which have important function as continuous phase during encapsulation (Vega & Roos, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Proteins are macromolecules which interact differently with water from small carbohydrates molecules (Swenson & Cerveny, 2015). Due to hydrophobic structures, proteins have poor miscibility and molecular segregation with aqueous carbohydrates (Halle, 2004;Roos & Potes, 2015). On the other hand, the presence of lipids in dispersed phase of carbohydrate-protein system slightly decreases T g (Potes, Kerry, & Roos, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This result can be as a result of separate phases formed by sugars and water and high‐molecular‐weight components present in the frozen solution (Ohkuma et al., 2008; Telis & Sobral, 2002). Roos and Potes (2015) also reported that there were two separate glass transitions, including the different roles of hydrated whey protein and sugar vitrification, in the maximally freeze‐concentrated phase of ternary glucose‐fructose‐bovine milk whey protein isolate‐water (GF‐BWP‐water) systems. They observed that GF‐BWP‐water systems showed a glass transition for the sugars determined by DSC and an α‐relaxation (glass transition) at the E″ peak temperature for protein hydration water measured by DMA.…”
Section: Thermal Transitions Affected By Food Componentsmentioning
confidence: 99%